The Relationship Between Diabetes Self-Management and Blood Glucose Control in Patients With Type 2 Diabetes Mellitus in Ulee Kareng Subdistrict, Banda Aceh - Saminan Saminan; Naufal Rabbany; Zahratul Aini; Zulkarnain Zulkarnain; Cut Murzalina (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
Diabetes mellitus is a type of chronic disease that is non-transmitted. Aceh province is the province with the seventh-highest prevalence of diabetes mellitus in Indonesia at 2.4%. People with type 2 diabetes mellitus are at risk of various complications and can cause death. Self-management of diabetes is one of the things that can be done by people with diabetes mellitus in controlling various complications. This study aimed to find out the relationship between diabetes self-management and blood glucose control of type 2 diabetes mellitus patients in Ulee Kareng Subdistrict, Banda Aceh. This type of sampling method in this research was cross-sectional with the number of samples in this study as many as 88 respondents. The study was conducted using the DSMQ questionnaire filling method to assess diabetes self-management level and blood glucose level value when respondents assess blood glucose control. The results of the study obtained are 30.7% of respondents have a good level of diabetes self- management, 44.3% enough, and 25% bad. As for blood glucose control, 65.9% of respondents had uncontrolled blood glucose levels, and 34.1% controlled. The results of the chi-square test obtained a p-value of 0.000 and the spearman correlation test obtained a p-value of 0.000, as well as a correlation coefficient of 0.492. Based on the data analysis, it can be concluded that there is a significant relationship between moderate and unidirectional levels between diabetes self-management and blood glucose control of type 2 diabetes mellitus patients in Ulee Kareng Subdistrict, Banda Aceh.